1998
DOI: 10.1002/(sici)1097-0363(19980915)28:3<477::aid-fld725>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in partially cooled tilted cavities

Abstract: Two‐dimensional numerical simulations of laminar natural convection in a partially cooled, differentially heated inclined cavities are performed. One of the cavity walls is entirely heated to a uniformly high temperature (heat source) while the opposite wall is partially cooled to a lower temperature (heat sink). The remaining walls are adiabatic. The tilt angle of the cavity is varied from 0° (heated from left) to −90° (heated from top). The fast false implicit transient scheme (FITS) algorithm, developed ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, to our best knowledge, partially cooled right-angle trapezoidal enclosure has not been considered yet. The application of partially cooled boundary condition can be found in the papers by El-Refaee et al [27] and Oztop [28]. Thus, the main objective of this paper is to examine the natural convection in a right-angle cavity filled with a porous medium and which is partially cooled from the inclined wall.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our best knowledge, partially cooled right-angle trapezoidal enclosure has not been considered yet. The application of partially cooled boundary condition can be found in the papers by El-Refaee et al [27] and Oztop [28]. Thus, the main objective of this paper is to examine the natural convection in a right-angle cavity filled with a porous medium and which is partially cooled from the inclined wall.…”
Section: Introductionmentioning
confidence: 99%
“…However, their values are decreased as aspect ratio increased. Computational results of Prasad and Kulacki [22] for partially heated from the bottom wall support this observation. Because, heat source is loosed more and more energy when the end walls are moved away from the leading edge of the heated segment.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that a plume-like flow occurs above the heated region with the increasing of Rayleigh number. El-Refaee et al [22] applied the fast false implicit transient scheme (FITS) algorithm to simulate natural convection in a tilted and partially cooled rectangular enclosure filled with non-porous medium. Their results show that both aspect ratio and inclination angle have significant effect on natural convection heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that inclination angle is the dominant parameter on heat transfer and fluid motion. El-refaee et al [19] studied the laminar natural convection in partially cooled tilted cavities. They concluded that the effects of aspect ratio and tilt angle on the rate of heat transfer becomes less significant with smaller values of opening ratio.…”
Section: Introductionmentioning
confidence: 99%